Rescaling Urban Governance : Planning, Localism and Institutional Change - Sturzaker, John (Book collections on Project MUSE., 2020)
Providing new research and thinking about cities, their governance and planning reform, this book compares the UK with multiple international examples in order to examine cutting-edge experimentation and innovation in new models of governance and urban policy in response to today's increasing global social and environmental challenges.